The institutional work of creating and implementing Social Impact Bonds. (26th April 2019) - Lowe, Toby; Kimmitt, Jonathan; Wilson, Rob; Martin, Mike; Gibbon, Jane
Abstract : Social Impact Bonds (SIBs) are a new and increasingly popular public policy tool which link payments to outcomes thus, in theory, transferring risk from governments to private investors. This paper draws on the concepts of institutional work and discursive institutionalism to analyse how a SIB influenced the rules, norms and decisions of key actors. It identifies two dominant discourses. One focused on addressing the social determinants of health, the other on creating the financial structure needed to run a SIB. These discourses were congruent at a macro-policy level, but tensions emerged between them at the meso and micro levels. This exemplifies the interdependence of structure and agency in institutional work and the mediating role which discourse plays. It also suggests that the effectiveness of a SIB depends not just on whether it achieves its outcome targets but also on whether it can institute new sets of practices and thinking.